Development of tricyanofuran-based activity probes for sulfatase assay in live cells. (September 2022) - Yoon, Hey Young; Lee, Jung Hoon; Park, Seung Bin; Choi, Sang-Hyun; Lee, Jun-Seok; Hong, Jong-In
Abstract: Sulfatase plays a pivotal role in the regulation of biologically active metabolites associated with various diseases. In particular, the up-regulation of steroid sulfatase activity has a positive correlation with breast cancer due to the increment of estrone levels via the desulfation reaction of estron 3-sulfate. Despite the high association between sulfatase activity and disease occurrence, there has been little progress in the discovery of sulfatase inhibitors, possibly due to the lack of robust activity-based assays. To design a sulfatase activity probe, we examined the binding between four fluorophores (coumarin, BODIPY, rhodol, and tricyanofuran [TCF]) and three isoforms of sulfatase using docking simulations and found that the rhodol and TCF scaffolds exhibited stable binding. To avoid the charge-driven organelle accumulation bias, we chose TCF as the core structure and designed two probes containing sulfate (TCF-OSulf and TCF-NCOO-OSulf ). The TCF probes showed clear colorimetric response and 2.7-fold and 5-fold fluorescence enhancements in vitro . In addition, the probes detected the inhibition of the enzyme by estrone- O -sulfamate (EMATE) in a time-dependent manner. Since cell-based screening has many advantages over the traditional high-throughput assay in vitro, we further examined TCF probes for the inhibitor assay for sulfatase activity in live cells. Based on our observations, TCF-NCOO-OSulf could be used to monitor sulfatase activity in live cells at a concentration of 5 μM. This is the first sulfatase activity-based probe that can visualize activity and inhibition in live cell conditions. Graphical abstract: Image 1 Highlights: Sulfatase probes were developed using TCF scaffold. TCF-OSulf and TCF-NCOO-OSulf had longer emission wavelengths than the traditional sulfatase probes, such as 4-MUS. Live cell imaging showed that TCF-NCOO-OSulf had a strong fluorescence and was sensitive to sulfatase activity.